Enrichir la compréhension de l’identité professionnelle du personnel enseignant du secteur technique au collégial par une prise en compte de la recherche sur la formation professionnelle : résultats d’une revue narrative systématisée - Zarié, Alexandre; Viau-Guay, Anabelle; Hamel, Christine (Canadian Journal of Education/Revue canadienne de l'éducation, 2025)
Unlike vocational and technical education (VTE), the topic of professional identity (PI) among teachers in technical education at the college level has received scant research attention. This article aims to deepen the understanding of the PI of teachers in technical education at a CEGEP (Collège d’enseignement général et professionnel) level by analyzing the results of research in vocational and technical training in Quebec, Canadian, and international contexts. It presents the results of a systematized review conducted in doctoral research. All the articles included in this review (n = 61) were analyzed using a mixed coding approach. The results show that teachers define themselves more by their disciplinary expertise than by their pedagogical expertise. Conversely, an identity based solely on the pedagogical dimension can lead to a weak actualization of professional knowledge. Therefore, the development of a dual identity integrating both pedagogical and professional dimensions is essential to adapt to changes in the world of work and education. This PI is dynamically constructed through social and individual factors via a process of interpretation and reinterpretation of experiences arising from practice.